Relationship of slope, soil type,and land use on erosion hazards - Parlin Hotmartua Putra Pasaribu (Inovasi, 2022)
Erosion is the process of eroding the top soil which is influenced by various factors such as slope, soil type, and land use type. This study aims to examine the relationship of these three factors to the erosion hazard, the results of which are used as the basis for determining the type of land conservation practice. Data were analyzed by Pearson correlation analysis. The results of the study indicate that the slope factor has a significant influence on erosion hazard with a correlation coefficient value of 0.777 and the category of the relationship is very close (very strong) with a positive direction. Meanwhile, soil type and land use type have no significant effect with a very weak correlation coefficient (0.047 for soil type, and 0.129 for land use type). However, based on the notation of direction, there is a positive direction for these two factors. Practices suggest both vegetative and mechanical methods for each type of land use. Conservation on land use utilization, namely the application of drainage channels and cover crops. The practice of conservation of secondary forest land use is the enrichment of forest plants. Conservation practices on scrub land use are reforestation and contour planting. Conservation practices in the use of dry land are intercropping, using mulch, planting parallel to the contours, terraces of mounds, and escape channels. Some of these conservation practices are useful for various parties in managing and conserving land resources. Keywords: Erosion, erosion factors, erosion hazard, conservation practices, conservation of land resources.